Incidence of Hemorrhagic Complications among Patients Treated with Thrombolytic in Erbil City, Iraq - Ahmed F. Hammad; Imad T. Abdulhafed; Abdulsalam R. Awad (Al-Anbar Medical Journal, 2020)
Background: Recombinant tissue-type plasminogen activator is an option of treatment for suspected occlusive vascular thrombi and its sequel (transmural myocardial infarction, pulmonary embolism, and ischemic stroke). The most important concern associated with those patients is the fear of hemorrhagic complications. Objectives: To evaluate the incidence and risk factors of bleeding following the use of recombinant tissue-type plasminogen activator. Materials and Methods: This prospective study was conducted in the Intensive Care Units of Roj-halat Emergency Hospital and Rizgary Teaching Hospital in Erbil city/Iraq. The duration of the study was through the period from 1st of June, 2016 to 1st of March, 2017. A convenient sample of 100 patients was selected. The patients were followed after their admission to Intensive Care Units for 24 hours after their treatment with recombinant tissue-type plasminogen activator to explore their complications. Results: Bleeding complication represented 10% of patients treated with recombinant tissue-type plasminogen activator (50% for each major and minor bleeding). There was a significant association between increased age of patients treated with recombinant tissue-type plasminogen activator and bleeding (P-value = 0. 01). Patients with a history of hypertension, diabetes, and smoking were significantly associated with a bleeding complication of recombinant tissue-type plasminogen activator (P-value <0.05). Conclusions: The incidence of bleeding among patients after treatment with recombinant tissue-type plasminogen activator in the intensive care unit was acceptable. The age, diabetes, smoking, and hypertension were risk factors for increasing the bleeding complications in subjects treated with recombinant tissue-type plasminogen.